2012
DOI: 10.1371/journal.pone.0037305
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Evolution and Genome Miniaturization in Minifish

Abstract: Background Paedocypris is a newly established genus of fish in Southeast Asia. Paedocypris is characterized by several unique features, including a tiny adult size (thus named miniature fish or minifish), fragmentary habitats of acidic peat blackwater swamps, an unusual reproduction mode and truncated development. These peculiarities lend themselves excellent for studying chromosome evolution and rapid speciation in vertebrates but also make them highly controversial for the phylogenetic position.Methodology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Cyprinid fishes show great cytogenetic variation. Their chromosome numbers range from 2 n = 42 ( Acheilognathus gracilis [52], or 2 n = 30 if the taxonomically controversial Paedocypris carbunculus is placed within Cyprinidae [53]) to 2 n = 417–470 ( Ptychobarbus dipogon [54,55]), with a mode at 2 n = 50, followed by 2 n = 48 [56]. Thus, it has been suggested that the ancestral karyotype of cyprinid fishes was 2 n = 48–50, and that polyploidisation occurred in several groups within the Cyprinidae [57-63].…”
Section: Discussionmentioning
confidence: 99%
“…Cyprinid fishes show great cytogenetic variation. Their chromosome numbers range from 2 n = 42 ( Acheilognathus gracilis [52], or 2 n = 30 if the taxonomically controversial Paedocypris carbunculus is placed within Cyprinidae [53]) to 2 n = 417–470 ( Ptychobarbus dipogon [54,55]), with a mode at 2 n = 50, followed by 2 n = 48 [56]. Thus, it has been suggested that the ancestral karyotype of cyprinid fishes was 2 n = 48–50, and that polyploidisation occurred in several groups within the Cyprinidae [57-63].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liu et al . () studied the chromosome structure in two species of the genus Paedocypris ( Paedocypris carbunculus Kottelat & Britz, 2008 and Paedocypris sp. Singkep).…”
Section: Mayden and Chen's New Family Group Names And Comments On Recenmentioning
confidence: 99%
“…The very low DNA content per cell of 0.36 pg, indicating a genome size of approximately 350 Mb in Paedocypris [compared with 0.34 pg in Sphoeroides spengleri (Bloch, 1785), the fish with the smallest genome reported to date] was interpreted by Liu et al . () as a case of genome miniaturization. Surprisingly, Liu et al .…”
Section: Mayden and Chen's New Family Group Names And Comments On Recenmentioning
confidence: 99%
See 1 more Smart Citation
“…In most fish chromosome preparation techniques, tissues are collected from different parts of the fish body, such as kidney (Blanco et al 2010;Poletto et al 2010;Martinez et al 2011;Liu et al 2012), liver (Affonso and Galetti 2005), spleen (Affonso and Galetti 2005), intestine (Kligerman and Bloom 1977), gill epithelium (Hashimoto et al 2009;Liu et al 2012), whole body (Shao et al 2010;Pradeep et al 2011), blood (Gold et al 1990;Eugenio et al 1993;Jacobina et al 2011), skin fibroblasts (Tantithakura et al 1993), bone marrow (Manosroi et al 2003), gonads (Liu et al 2012) and fin epithelium (Fontana et al 2008). The above preparation techniques involved the use of metaphase arresting agents, such as colchicine or colcemid.…”
mentioning
confidence: 99%